HOW THE HUMAN BRAIN PROCESSES LANGUAGE - Juraeva Sarvara Otabekovna; Xakimbayeva Ozoda Kalandarovna (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article examines how language influences human thinking from a psycholinguistic perspective. Drawing on the Sapir–Whorf hypothesis, it explores cross-linguistic research on perception, memory, and spatial reasoning. Differences in color naming, spatial orientation, and time concepts across languages are highlighted. The study shows that language guides attention and categorization, shaping thought without fully determining it, and underscores the importance of linguistic diversity in understanding cognition.